Lacrimal gland targeted therapies for refractory epiphora: quantitative changes in the gland activity - Singh, Swati; Bothra, Nandini; Ali, Mohammad Javed (Orbit, 2023)
Purpose: To investigate the effect of botulinum toxin (BTX) and partial orbital lobe dacryoadenectomy (POLD) on the main lacrimal gland functions using the direct assessment of its secretory activity. Methods: A pilot study involving 14 subjects (mean age, 42.16 years) with proximal bicanalicular block (n = 9) or complete punctal effacement (n = 5) received either intraglandular 2.5 units of BTX (n = 7) or underwent the POLD procedure (n = 7). Dynamic assessment of tear secretion from the palpebral lobes was performed as per standard protocols. The parameters studied included Schirmer I, changes in the glandular outflow, and the neurosensory secretory lag. Results: Schirmer I values showed a mean reduction of 5.25 mm (range, 2–8 mm) following BTX injection, and mean tear flow decreased from 1.46 (Formula presented.) to 1.11 (Formula presented.) (P = 0.15). The POLD group showed a significant mean reduction of 0.45 (Formula presented.) in mean tear flow at 1 month (P = 0.03) and 0.32 (Formula presented.) at 3 months of follow-up (P = 0.20). However, there was no statistically significant change of the Schirmer values in the POLD group at 3 months. Conclusion: Direct assessment of lacrimal gland function can be used to monitor changes following the gland therapies. Although POLD shows a significant reduction in short term, significant surgical improvisation would be needed for it to be effective in long term. A larger study is ongoing to further our understanding.
CRIS-Team Scopus Importer:2023-05-26
Keywords: botulinum toxin; canalicular obstruction; dacryoadenectomy; epiphora; Lacrimal gland